3. Describe what is being done in each step while solving the
equation.
2(- 3x + 4) = 5x + 2
- 6x + 8 = 5x + 2
8 = 11x + 2
6 = 11x
e)
x = í

3 Describe what is being done in each step while solving the equation 2 3x 4 5x 2 6x 8 5x 2 8 11x 2 6 11x e x í class=

Respuesta :

solime
From a) to b), you expand the brackets, which is -6x+8.

From b) to c), you bring -6x to the other side of the equation.

By bringing it to the other side, -6x becomes +6x.

You then do 5x+6x, which is 11x.

From c) to d), you bring +2 to the other side of the equation.

By bringing it to the other side, +2 becomes -2.

You then do 8 - 2, which is 6.

From d) to e), in order to get x by itself, you divide it by 11, hence 6/11.

This makes the equation become x = 6/11.


Sorry if that made no sense
ACCESS MORE

Otras preguntas